BAGAIMANA CONSUMER PERCEPTION DAN CONSUMER ATTITUDE MEMPENGARUHI MOTIVASI PEMBELIAN GREEN PRODUCT (KAJIAN PERILAKU KONSUMEN DARI BERBAGAI BUDAYA DAN NEGARA) - Novia Astri Leonora (Universitas Trunojoyo Madura, 2018)
ABSTRACTCurrently, the environmental damage occurs almost throughout the earth. Many people try to find the way to save the environment. It causes the companies to make green products in the contribution of protecting the environtment. But not everyone can accept the green product. This study case choosesvarious countries, such as Niger, China, United States, India, Lesotho, Italia, Sweden, South Korea, and Hong Kong. Not all countries have good perception and good attitude towards green products, but most of them have good perception towards green products and they have good attitude if the green products can give them a benefit. Marketers can give more education about green product to countries which have negative perception and negative attitude towards green product. Marketers also have a big opportunity to market their green product to countries which have a positive perception and positive attitude toward green products